Higher Education as a Concept of Common Good: The Challenge Posed by UNESCO - Licandro, Oscar Daniel (2018)
The 2015 UNESCO’s call for the conceptualization of Higher Education (HE) as a common good opens doors to a new perspective for the understanding and search of a solution to a set of problems stemming from its increasing privatization. For this call not to remain as a mere speech and be able to produce a real transforming impact, it needs to reflect on the theoretical and practical implications of this new way of conceptualizing HE. A new theoretical framework and practical tools need to be built so as to migrate from the current forms of HE governance, designed to manage a public good, towards the specific forms of governance of common goods. This document discusses UNESCO’s call as having a solid theoretical foundation, for which a bibliographical review on the theory of the common goods is performed, demonstrating that Higher Education can be, indeed, considered as such. This work reflects, also, on the impact of this re-conceptualization on the governance of HE and on the changes to be introduced to it. This work concludes suggesting that the theoretical and methodological framework of University Social Responsibility contributes a base on which to build those changes.